Save the World with Code : 20 Fun Projects for All Ages Using Raspberry Pi, micro:bit, and Circuit Playground Express - Underwood, Lorraine (McGraw-Hill Education TAB, 2020)
This fun project book engages kids with coding and making This easy-to-follow guide offers a fun, hands-on introduction to coding for kids and anyone looking for a whimsical, light-hearted approach to making. The book contains 20 cool projects that use Raspberry Pi, micro:bit, and kid-friendly Circuit Playground Express along with a few inexpensive, easy-to-find parts like LEDs and tin foil. Save the World with Code: 20 Fun Projects Using Raspberry Pi, micro:bit, and Circuit Playground Express for Kids features projects ranging from easy to advanced. You will get a fun blend of environmentally friendly projects, like a thermometer to monitor home temperature and a moisture sensor for keeping your plants watered, with more wacky projects, like a light up sword, cookie theft detector, and a touch sensor to check if someone is a zombie! " eaches kids coding basics using Raspberry Pi, micro:bit, and Circuit Playground Express " ach project includes a parts list, illustrations, and easy-to-follow assembly instructions " ritten by a maker and educator whose goal is to make coding fun for everyone